Peran Knowledge Sharing dan Absorptive Capacity dalam Meningkatkan Kinerja Inovasi UKM - Okta Rashima Nugraha; Arif Hartono (UNIVED Press, 2022)
This study examines the role of knowledge sharing (KS) and absorptive capacity (AC) on Indonesian Small and Medium Enterprises (SMEs) innovation performance. In addition, this study tests the role of AC in mediating the relationship between KS and innovation performance. This study used quantitative research method and data was collected using questionnaires. Samples in this study are SMEs located in Bayat District, Klaten Regency, Central Java, Indonesia which are engaged in pottery, batik and household appliances. Purposive sampling method was employed, and a total 150 samples was successfully collected. Structural Equation Modelling (SEM) was used to test the proposed hypotheses. The results of this study are as follows: (1) KS positively and significantly affects AC and innovation performance. (2) AC positively and significantly influence innovation performance. (3) Lastly, AC also successfully mediates the relationship between KS and innovation performance.